(952) The Financial System of the G.D.R النظام المالى في جمهورية ألمانيا الديمقراطية - Heinz Joswig. (INP, 2024)
The most important role of the financial system is to enhance the efficiency of the national economy and to secure the activities of the state. In the German Democratic Republic (GDR), the political power of workers and collective farmers is exercised in cooperation with intellectuals and other working people. The economic basis is socialist ownership of the means of production, existing in two forms: nationally-owned and cooperative. In the GDR, state property, or nationally-owned property, is the predominant form of ownership, reflecting the development of socialist ownership and its significance as expressed in the share of national income.